Price-Taking Behavior - Johansen, Leif (Econometrica, 1977)
[A recent paper by D. J. Roberts and A. Postlewaite [1] shows a possible justification for the assumption that participants in a market behave as price-takers when the number of participants becomes large. The present note compares this justification with other approaches to the same question and argues that the various approaches are complementary rather than alternative since, in order to demonstrate the viability of a system with price-taking behavior, all types of feasible deviations from such behavior must be explored. The note introduces a taxonomy for such deviations which may be useful in comparing various approaches and contributions found in the literature.]